Clinical and radiological efficacy of single-dose intra-articular high-molecular-weight hyaluronic acid in knee osteoarthritis - Anjana Babu; Chethan Channaveera; Ajay Gupta; Mahesh K. Mittal; Deepthi S. Johnson (Journal of Family Medicine and Primary Care)
Context: While visco-supplementation is being used for the treatment of knee osteoarthritis (OA), the published reports vary widely in benefits afforded by this treatment. It was therefore proposed to assess the objective parameters along with subjective outcomes. Aims: Our study assessed the radiological and clinical efficacy of single-dose high-molecular-weight intra-articular hyaluronic acid (HMW-IAHA) injection in knee OA. Settings and Design: This interventional cohort study was conducted in a calculated sample size of 44 patients with knee OA. Materials and Methods: Visual analog scale (VAS) and knee OA and outcome score (KOOS) were used for clinical assessment, and whole organ magnetic resonance imaging score (WORMS) for radiological assessment. The subjects were given a single dose of HMW-IAHA injection, 90 mg/3 ml, and were assessed on day 0 and day 90. Statistical Analysis: Statistical Package for Social Sciences (SPSS) software was used. Results: At the day 90 follow-up, there was an improvement in mean ± standard deviation values of VAS score (day 0: 8.53 ± 0.81, day 90: 5.97 ± 0.87), KOOS score (day 0: 27.33 ± 15.18, day 90: 57.26 ± 14.26), and the cartilage signal and morphology in the medial femorotibial joint (day 0: 11.02 ± 6.26 and day 90: 10.91 ± 6.22) and patellofemoral joint (day 0: 10.35 ± 4.36 and day 90: 10.28 ± 4.39) compartments. There was a decrease in synovitis score from 2.3 ± 1.61 to 1.3 ± 1.3 in the medial femorotibial joint compartment and total WORMS score (day 0: 66.57 ± 36.06, day 90: 65.14 ± 35.62). Conclusions: A single dose of intra-articular injection with high-molecular-weight hyaluronic acid produces improvement in the clinical symptoms and quality of life as well as is effective in maintaining the articular cartilage integrity and reducing synovial inflammation.